Effect of Profitability on Stock Prices of Transportation Companies in Indonesia - Linzzy Pratami Putri; Rahmansyah Ritonga (AIBPM Publisher, 2019)
The purpose of this study was to determine and analyze the effect of Gross Profit Margin on stock prices, to determine and analyze the effect of Net Profit Margin on stock prices, to determine and analyze the effect of Return on Asset on stock prices, to determine and analyze the effect of Return on Equity on stock prices and to find out and analyze the effect of Cross Profit Margin, Net Profit Margin, Return On Assets Ratio and Return On Equity on stock prices both partially and simultaneously on Transportation Companies Listed on the Indonesia Stock Exchange for the period 2013-2017. The approach used in this study is associative approach. The population in this study are all Transportation Companies Listed on the Indonesia Stock Exchange while samples that meet the criteria for sampling observations carried out for five years and as many as seven Transportation Companies Listed on the Indonesia Stock Exchange. Data collection techniques in this study used documentation techniques. The data analysis technique in this study used the Classical Assumption Test, Multiple Regression, Hypothesis Test (t Test and F Test), and the Determination Coefficient. Processing data in this study using the SPSS (Statistical Package for the Social Scoring) software version 24.00. The results of this study prove that partially there is a significant positive effect of Gross Profit Margin on stock prices. There is a significant negative effect on Net Profit Margin on stock prices. There is a significant positive effect of Return On Assets on stock prices. There is no effect of Return On Equity on stock prices. Simultaneously there is a positive and significant influence of all variables affecting the stock price of transportation companies listed on the Indonesia Stock Exchange.